Impact of Global Energy Index and Crude Oil & Coal Price to Indonesia Stock Indices - Ghani Fikri Yasri; Eka Pria Anas (Green Publisher Indonesia, 2023)
Oil prices have stagnated from 2015 to early 2020. After the crisis caused by Covid-19, oil prices slowly increased and even reached their highest point in the last 10 years in mid-2022. Coal prices reached an all-time high at the end of 2021 before then increasing again in early 2022. The significant increase in coal and oil prices was triggered by the war between Russia and Ukraine. The embargo on Russian oil and coal has contributed to the decline in coal and oil stocks as fuel for power plants in Europe. This research determines the impact of the volatility of oil prices, coal prices, and global energy price index on the stock price index in Indonesia. Does global energy price index, which consists of crude oil and coal prices affect Indonesia stock indices more precisely. This study show volatility of oil prices and coal prices affects company stock prices in Europe. The analysis examined Jakarta Composite Index, LQ45 Index, Jakarta Islamic Index, and Sectoral Index for the 2018-2022 periods. Several techniques, including ordinary least square, linear regression, and multiple regression. The increases of the oil prices, coal prices, and global energy indices affect the stock price index in Indonesia. The study will help investor to understand the impact of oil, coal price volatility and global energy index to several Indonesia stock indices.